A essência do cuidado à criança com asma - Siqueira, Karina Machado (2014)
Among the chronic diseases that affect children's health, asthma deserves special mention because of its high prevalence and the impact it can have on a child's life. Given its complexity, the care of children with asthma should be shared between the family and a team of health professionals trained for this purpose. This study aimed to unveil facets of the essence of this care, according to the perceptions and experiences of children and their families. For value conscious experience of people, the phenomenology was chosen as theoretical and methodological referential. Through this approach, was possible to shed light to what is essential in the care of these children and advance in the elucidation of this phenomenon, from its intentional structure. The care was taken as the centerpiece of discussions and, accordingly, became appropriate appeal to think of Martin Heidegger, in order to enlarge the possibilities of understanding and discuss some issues that converge to the phenomenology of care. Participated in the survey five families of children with moderate or severe asthma, aged between seven and ten years, attending in a outpatient clinic specializing in childhood asthma, located in Goiânia-GO. Data collection occurred during home visits between September 2013 and January 2014. Initially were elaborated genograms and ecomaps representing families and, then, were made interviews with children and family, mentioned as participants in care. Descriptions expressed were analyzed according to the Method of Qualitative Analysis of Situated Phenomenon. The invariant structure of the phenomenon directed to three major themes: Being with a child with asthma; The family care to children with asthma; Be children with asthma: particularities and restrictions. Data analysis aggregated relevant aspects for the understanding of the essence of the care of children with asthma and were presented in the form of articles. The joint construction of genograms and ecomaps favored the approximation with families and facilitated the conduct of interviews according to the phenomenological method. The results enabled us to understand that the established relationships with the child, the members of the family unit, health services and religious institutions stood out as sources of support for care. The school was presented as a space of relevance, which found support, but also experienced situations of embarrassment and exclusion. Family members described their anxieties, fears and difficulties, especially during asthma attacks. Highlighted particularities and restrictions in the lives of children and in family environment, and described attitudes of protection. Emerged the difficulty of children in dealing with some fears, frustrations and constraints related to the disease and treatment, but also became clear their strengths and their families’ strengths to take care of more autonomous and effectively way. The study revealed that knowledge about the experiences of families provides important information for health professionals that work within the context of childhood asthma and may contribute to better understanding of the proposed interventions, promoting new strategies of attention.